Co-Creation Activity as Moderator in the Destination Brand Attachment Model towards Customer Intention to Revisit Destination in Indonesia and Timor Leste - Bramantyo, Paskalis Dio; Fernando, Ricky; Utami, Christina Whidya; Sumaji, Yoseva Maria (International Business Management - Universitas Ciputra, 2024)
This research aims to develop a model by examining the impact of perceived quality on destination brand attachment, destination brand attachment on memorable customer experience, and memorable customer experience on the intention to revisit. It also explores whether co-creation activity moderates the relationship between memorable customer experience and the intention to revisit. The method involves purposive sampling, targeting youths aged 20-40 who have visited hospitality locations in Indonesia and Timor-Leste at least three times in the last three months. The sample includes 175 respondents from Indonesia and 75 from Timor-Leste. The results show that perceived quality significantly impacts destination brand attachment, which in turn significantly affects memorable customer experience. This experience significantly influences the intention to revisit, with destination brand attachment also showing a significant impact. Additionally, co-creation activity moderates the influence of memorable customer experience on the intention to revisit in Indonesia, but not in Timor-Leste. This research contributes to theoretical knowledge and offers practical insights for entrepreneurs in the hospitality industry, providing new perspectives for strategic decision-making.